An automated workflow to compile multibeam bathymetric data from multiple cruises: The Northwest African continental margin - Qinqin Tang; Jens Schneider von Deimling; Jacob Geersen; Sebastian Krastel (Marine Geophysical Research, 2026)

Recurrent glide planes suggest a climatic control on pre-conditioning slope stability offshore the Northwestern Africa - Qinqin Tang; Jacob Geersen; Christoph Böttner; Sebastian Krastel (Geo-Marine Letters, 2026)

Patient Experiences and Expectations Regarding Erectile Dysfunction Education Prior to Rectal Cancer Surgery: A Qualitative Study - Sebastian Borgund Hansen; Siv Fonnes; Birthe Thing Oggesen; Susanne Vahr Lauridsen; Jacob Rosenberg (Journal of Cancer Education, 2026)
Erectile dysfunction is common after surgery for rectal cancer with a prevalence of moderate to severe erectile dysfunction up to 35%. Preservation of sexual function is regarded as a core outcome in colorectal surgery. We wanted to investigate male patients’ perspectives on preoperative education about the risk of erectile dysfunction after surgery for rectal cancer. Using an interview guide, we performed individual semi-structured interviews with male patients who had surgery for rectal cancer within the past 3–12 months. The interviews were transcribed, condensed, coded, and analyzed with inductive qualitative content analysis. We interviewed 13 male patients. Their perspectives were condensed in four main themes: importance of a partner to be present at the preoperative counseling; information as crucial; wishful thinking as a coping strategy; and the need for direct information to avoid unrealistic expectations. Patients described general gratitude across the entire process but a lack of follow-up regarding erectile function. Surgeons should actively engage in a discussion with patients regarding the risk of developing erectile dysfunction. Importance might differ since patients have different preoperative erectile functions and different postoperative needs. A partner or close relative should participate in the preoperative counseling.

Adhesion-adapted polymer coating systems as filmic model systems for homogeneous geometry-independent surface coating for cleaning analyses - Susanne Höhne; Petra Uhlmann; Vincent Eisenrauch; Sebastian Jacob; Carolin Böhm; Hannes Kettner; Eva Bittrich; Enrico Fuchs; Jens-Peter Majschak; Marc Mauermann (Food and Bioproducts Processing, 2026)

Induction of human cytochrome P450 enzyme activities by metabolism disrupting chemicals in the hepatic cell line HepaRG - Elodie Person; Nicolas J. Cabaton; Laurie Urien; Marlène Z. Lacroix; Jorke H. Kamstra; Louisa Mediouni; Barbara Kubickova; Agnès Jamin; Sylvie Chevolleau; Sebastian Hoffmann; Juliette Legler; Miriam N. Jacobs; et al. (Toxicology, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Coastal zones of the Baltic Sea in the Anthropocene: Current state and the impact of climate change - Maren Voss; Peter Holtermann; Soeren Ahmerkamp; Damian Leonardo Arévalo Martínez; Bronwyn Cahill; Manita Chouksey; Joachim W. Dippner; Jörg Dutz; Peter Feldens; Jacob Geersen; Kaja Gentsch; Mayya Gogina; et al. (Estuarine, Coastal and Shelf Science, 2025)

Long-term cheatgrass (Bromus tectorum L.) control increases shrub leader growth and mule deer (Odocoileus hemionus) visitation - Jacob S. Courkamp; James R. Sebastian; Joseph K. Swanson (Rangelands, 2025)

A Comprehensive Database of Expert‐Curated Occurrences for the Genus Carex L. (Cyperaceae) - María Sanz‐Arnal; Pablo García‐Moro; Carmen Benítez‐Benítez; Marina Coca‐de‐la‐Iglesia; Angélica Gallego‐Narbón; Consolación Barciela; Fabrizio Bartolucci; Prabin Bhandari; Matthew Bradley; Asunción Cano; Antoine Derouaux; Sabina Donadío; et al. (Global Ecology and Biogeography, 2025)
Motivation Geographic occurrences are essential for biodiversity studies, but publicly available repositories like GBIF often contain errors and biases, especially for taxonomically complex groups like Carex L. (Cyperaceae). This work provides an expert‐curated global dataset of occurrences compiled from different sources to enhance data accuracy and usability. The final dataset includes 384,067 occurrences of 1790 Carex species. Main Types of Variables Contained The dataset includes species occurrence records with geographic coordinates, taxonomic identifications, and curation flags (e.g., introduced, erroneous records). Spatial Location and Grain The dataset covers a global scale, using the WGS84 projection. Spatial resolution is standardised to a minimum of three decimal degrees (~1 km, if possible). Time Period and Grain Online records span from 1950 to 2020, but some manually georeferenced records are earlier (1850). There is also fieldwork data after 2020, specifically up to 2023. Major Taxa and Level of Measurement Cyperaceae: Carex . Most records have species‐level identification, and some of them are identified at subspecies or variety levels. Software Format Data are supplied as comma‐separated values files with UTF‐8 encoding.

IMU-augmented Patient-related Outcome Measure for Knee Arthroplasty Patients - Ted Yeung; Sabina Yang; Shasha Yeung; Faseeh Zaidi; Sebastian Weaver; Scott Bolam; Megan Lovatt; Thor Besier; Jacob Munro; Michael Hanlon; Paul Monk; Justin Fernandez (Journal of Medical and Biological Engineering, 2025)
Purpose The aims of this study are (1) to derive a set of time series features to predict the total knee contact force during gait from two ankle-mounted inertial measurement units (IMUs); and (2) to explore the best combination of PROMs and IMU-derived, biomechanical measures for the prediction of postoperative quality of life (QoL) and reduce the inconsistency between biomechanical and PROMs. Methods Synced motion capture (optical and inertial) data were collected from four healthy participants to obtain a suitable time-series feature set that relates to knee contact forces (KCF). Then, using data from 28 patients during overground walking, we generated linear and random-forest regressor models for estimating QoL. These models were evaluated using temporal cross-validation. Results Overall, features from the IMUs could predict the total KCF (R 2 > 0.90, RMSE = 0.14, %BW). A machine learning model was trained on the data obtained during the recovery (up to 1 year) to predict EQ-5D-5 L score (patient QoL). The models were able to predict within a margin of 1.81–4.40 units of the actual score 95% of the time. Conclusion The presented study derives surrogate measures of total knee contact force (KCF) using ankle-mount IMUs. We identified the best combination of PROMs and IMU-derived measures for postoperative QoL at four time-points. The optimal metrics varied for each time point: OKS only, knee kinematics with OKS, KCF with OKS, and KCF only. Further data collection will be required to compile a comprehensive dataset to generate a robust predictive model.

Epistemological dimensions of Indigenous honey collection in the Kattunaicken community of South India - Antony Jacob Sebastian (Conservation Biology, 2025)
Indigenous ecological knowledge (IEK) has proven effective in environmental governance, forest management, and sustainable development, yet it is threatened by globalization and rapid social–ecological changes. In southern India, I investigated the engagement of the Kattunaicken community with the forest, particularly through honey collection, to explore the connection between their Indigenous epistemological identity and their role in caring for the forest and its inhabitants. I conducted 48 interviews and accompanied 11 forest walks as part of walking ethnography with male community members, who are primarily involved in honey collection within the Wayanad district of Kerala. The Kattunaicken identity was intrinsically linked to their knowledge of the forest, with reciprocal epistemological interactions between the community and forest entities (trees, animals, and bees). Honey collection emerged as an epistemological endeavor, manifesting their Indigenous identity through the collective “knowing” of the forest that encompassed sensorial, ethical, and metaphysical dimensions that facilitated harmonious coexistence and care for the forest and its inhabitants. The Kattunaicken world of knowing challenges extractivist interpretations of nontimber forest product collection, emphasizing the importance of Indigenous epistemologies in shaping alternative knowledge construction for forest conservation. Their epistemological framework highlights care as an active process emerging from collective understanding and negotiation among all entities within their shared epistemic realm, fostering a harmonious coexistence that transcends conservation efforts.

Probability of extinction and peak time for multi-type epidemics with application to COVID-19 variants of concern - Jacob Curran-Sebastian; Louise Dyson; Edward M. Hill; Ian Hall; Lorenzo Pellis; Thomas House (Journal of Theoretical Biology, 2025)

Volcanic eruptions and the global subsea telecommunications network - Michael A. Clare; Isobel A. Yeo; Jacob Nash; James E. Hunt; Semisi Panuve; Alasdair Wilkie; Rebecca Williams; Natasha Dowey; Peter Rowley; Jennifer Barclay; Jeremy Phillips; Jazmin Scarlett; et al. (Bulletin of Volcanology, 2025)
When the first transoceanic telegraph cables were laid in the mid-1800s, rapid communication between continents became possible. The advent of fibre-optic submarine cables in the 1990s catalyzed a global digital revolution. Today, a network of > 1.7 million kilometres of fibre-optic cables crosses the oceans, carrying more than 99% of all digital data traffic worldwide and trillions of dollars in financial transactions. These arteries of the global internet underpin many aspects of our daily lives, and are particularly important for remote island communities that rely on submarine cables for telemedicine, e-commerce, and online education. However, these same remote communities are often in seismically and volcanically active regions and can be prone to natural hazards that threaten their critical subsea communication infrastructure. This vulnerability was acutely exposed in January 2022, when the collapse of the eruption plume of Hunga Volcano triggered fast-moving density currents that damaged Tonga’s only international submarine cable, cutting off an entire nation from global communications in the midst of a volcanic crisis. Here, we present a new comprehensive analysis of damage to subsea communications cables by volcanic events from around the world, and document their diverse impacts. Examples include (i) severing of the telegraph cable crossing the Sunda Strait by a tsunami triggered by the 1883 Krakatau eruption, Indonesia; (ii) ocean-entering pyroclastic density currents, lahars, and landslides during the 1902 eruptions of Mount Pelée, Martinique, that damaged six telegraph cables; (iii) destruction of a cable landing station on Montserrat by a pyroclastic density current in 1997; (iv) submarine slope failure at Kick ‘em Jenny, Grenada, that damaged two fibre-optic cables; (v) complete loss of the telecommunications network due to power outages following the 2000 eruption of Miyake-jima, Japan; and (vi) disruption to subsea cables resulting from the 2021 eruption of La Soufrière, St. Vincent. We find that the causes of damage typically relate to secondary hazards that occur not only at the same time as the eruption climax, but also some time after. There does not appear to be an explosivity intensity threshold for cable-damaging events; however, the extent of damage may be related to the original volcano morphology (e.g. steep slopes), spatial location (e.g. near the coast or partially/totally submerged), the eruption size or explosivity, and/or volcanic depositional processes involved. Based on these diverse case studies, we present lessons learned for enhancing telecommunications resilience, and discuss how subsea cables themselves can be used as sensors to improve understanding and early warning of volcanic hazards, potentially filling a monitoring gap for remote island communities.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Can triad forestry reconcile Europe’s biodiversity and forestry strategies? A critical evaluation of forest zoning - Thomas A. Nagel; Mariano Rodríguez-Recio; Tuomas Aakala; Per Angelstam; Admir Avdagić; Zbigniew Borowski; Andrés Bravo-Oviedo; Gediminas Brazaitis; Thomas Campagnaro; Michał Ciach; Milic Curovic; Inken Doerfler; et al. (Ambio, 2025)
Balancing increasing demand for wood products while also maintaining forest biodiversity is a paramount challenge. Europe’s Biodiversity and Forest Strategies for 2030 attempt to address this challenge. Together, they call for strict protection of 10% of land area, including all primary and old growth forests, increasing use of ecological forestry, and less reliance on monocultural plantations. Using data on country wide silvicultural practices and a new database on strict forest reserves across Europe, we assess how triad forest zoning could help meet these goals. Our analysis reveals that zoning in Europe is overwhelmingly focused on wood production, while there has been little concomitant protection of forests in strict reserves. Moreover, most strict forest reserves are

Modelling the stochastic importation dynamics and establishment of novel pathogenic strains using a general branching processes framework - Jacob Curran-Sebastian; Frederik Mølkjær Andersen; Samir Bhatt (Mathematical Biosciences, 2025)

One to rule them all? Assessing the performance of sustainable forest management indicators against multitaxonomic data for biodiversity conservation - Yoan Paillet; Livia Zapponi; Peter Schall; Jean-Matthieu Monnet; Christian Ammer; Lorenzo Balducci; Steffen Boch; Gediminas Brazaitis; Alessandro Campanaro; Francesco Chianucci; Inken Doerfler; Markus Fischer; et al. (Biological Conservation, 2024)

Geomorphological evidence for volcano-tectonic deformation along the unstable western flank of Cumbre Vieja Volcano (La Palma) - Luisa Rollwage; Olga Sánchez-Guillamón; Christian Sippl; Ricardo León; Juan Tomás Vázquez; Morelia Urlaub; Felix Gross; Christoph Böttner; Sebastian Krastel; Jacob Geersen (Geomorphology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Weight of evidence evaluation of the metabolism disrupting effects of triphenyl phosphate using an expert knowledge elicitation approach - Claire Beausoleil; Anne Thébault; Patrik Andersson; Nicolas J. Cabaton; Sibylle Ermler; Bernard Fromenty; Clémentine Garoche; Julian L. Griffin; Sebastian Hoffmann; Jorke H. Kamstra; Barbara Kubickova; Virissa Lenters; et al. (Toxicology and Applied Pharmacology, 2024)

Avoiding a reproducibility crisis in regulatory toxicology—on the fundamental role of ring trials - Miriam N. Jacobs; Sebastian Hoffmann; Heli M. Hollnagel; Petra Kern; Susanne N. Kolle; Andreas Natsch; Robert Landsiedel (Archives of Toxicology, 2024)
The ongoing transition from chemical hazard and risk assessment based on animal studies to assessment relying mostly on non-animal data, requires a multitude of novel experimental methods, and this means that guidance on the validation and standardisation of test methods intended for international applicability and acceptance, needs to be updated. These so-called new approach methodologies (NAMs) must be applicable to the chemical regulatory domain and provide reliable data which are relevant to hazard and risk assessment. Confidence in and use of NAMs will depend on their reliability and relevance, and both are thoroughly assessed by validation. Validation is, however, a time- and resource-demanding process. As updates on validation guidance are conducted, the valuable components must be kept: Reliable data are and will remain fundamental. In 2016, the scientific community was made aware of the general crisis in scientific reproducibility—validated methods must not fall into this. In this commentary, we emphasize the central importance of ring trials in the validation of experimental methods. Ring trials are sometimes considered to be a major hold-up with little value added to the validation. Here, we clarify that ring trials are indispensable to demonstrate the robustness and reproducibility of a new method. Further, that methods do fail in method transfer and ring trials due to different stumbling blocks, but these provide learnings to ensure the robustness of new methods. At the same time, we identify what it would take to perform ring trials more efficiently, and how ring trials fit into the much-needed update to the guidance on the validation of NAMs.

Single-component multi-rate real time hybrid simulation pilot test on a composite structure - Jacob P. Waldbjoern; Sebastian Andersen; Jacob Herold Hoegh; Christian Berggreen (Engineering Structures, 2024)

Submarine canyon morphology along the Chilean marine forearc (19°S–45°S) - Shuang Li; Jacob Geersen; Sebastian Krastel; Wei Li (Geomorphology, 2023)

Symbiotic status alters fungal eco‐evolutionary offspring trajectories - Carlos A. Aguilar‐Trigueros; Franz‐Sebastian Krah; William K. Cornwell; Amy E. Zanne; Nerea Abrego; Ian C. Anderson; Carrie J. Andrew; Petr Baldrian; Claus Bässler; Andrew Bissett; V. Bala Chaudhary; Baodong Chen; et al. (Ecology Letters, 2023)
Despite host‐fungal symbiotic interactions being ubiquitous in all ecosystems, understanding how symbiosis has shaped the ecology and evolution of fungal spores that are involved in dispersal and colonization of their hosts has been ignored in life‐history studies. We assembled a spore morphology database covering over 26,000 species of free‐living to symbiotic fungi of plants, insects and humans and found more than eight orders of variation in spore size. Evolutionary transitions in symbiotic status correlated with shifts in spore size, but the strength of this effect varied widely among phyla. Symbiotic status explained more variation than climatic variables in the current distribution of spore sizes of plant‐associated fungi at a global scale while the dispersal potential of their spores is more restricted compared to free‐living fungi. Our work advances life‐history theory by highlighting how the interaction between symbiosis and offspring morphology shapes the reproductive and dispersal strategies among living forms.

Where are we now with European forest multi-taxon biodiversity and where can we head to? - Sabina Burrascano; Francesco Chianucci; Giovanni Trentanovi; Sebastian Kepfer-Rojas; Tommaso Sitzia; Flóra Tinya; Inken Doerfler; Yoan Paillet; Thomas Andrew Nagel; Bozena Mitic; Lourdes Morillas; Silvana Munzi; et al. (Biological Conservation, 2023)

Chitosan-based beads as sustainable adsorbents for wastewater remediation: a review - Akash Balakrishnan; Sowmya Appunni; Mahendra Chinthala; Meenu Mariam Jacob; Dai-Viet N. Vo; Soreddy Sainath Reddy; Emmanuel Sebastian Kunnel (Environmental Chemistry Letters, 2023)

Influence of steam-induced wetting of food- and cosmetic-based contaminants on the efficiency of clean-in-place processes of containers - Siegfried Beckmann; Enrico Fuchs; Sebastian Jacob; Marc Mauermann (Food and Bioproducts Processing, 2023)

The effect of relative humidity on eddy covariance latent heat flux measurements and its implication for partitioning into transpiration and evaporation - Weijie Zhang; Martin Jung; Mirco Migliavacca; Rafael Poyatos; Diego G. Miralles; Tarek S. El-Madany; Marta Galvagno; Arnaud Carrara; Nicola Arriga; Andreas Ibrom; Ivan Mammarella; Dario Papale; et al. (Agricultural and Forest Meteorology, 2023)

Assessment of defoliation and subsequent growth losses caused by Lymantria dispar using terrestrial laser scanning (TLS) - Martin Jacobs; Torben Hilmers; Benjamin M. L. Leroy; Hannes Lemme; Sebastian Kienlein; Jörg Müller; Wolfgang W. Weisser; Hans Pretzsch (Trees, 2022)
Key message TLS scans of three surveys before, during and after gypsy moth gradation, allowed high-resolution tracking of defoliation and subsequent inter-annual growth losses on an individual tree level. Abstract Foliation strongly determines all tree growth processes but can be reduced by various stress factors. Insect defoliation starts at variable times and is one stress factor that may affect photosynthetic processes and cause immediate reactions like refoliation, which are difficult to detect by surveys repeated at 1-year intervals. This study used a large-scale field experiment in German oak/mixed forests affected by gypsy moths ( Lymantria dispar ) to test the use of terrestrial laser scanning (TLS) for detecting inter-annual foliation and growth losses at the individual tree level caused by the gypsy moth. The experiment comprised two levels of gypsy moth defoliation risk, high (H) and low (L), as well as two pest control treatment levels: spraying with the insecticide Mimic (M) or unsprayed control (C). The factorial design consisted of four treatment combinations (HC, HM, LC, and LM), applied to 11 spatial blocks with a total of 44 plots. The TLS approach detected the defoliation caused by the gypsy moth, estimated as leaf area and crown perforation parameters. For the first time, TLS-derived tree foliation was evaluated based on inter-annual stem growth. Leaf area and crown perforation showed a correlation of + 0.6 and – 0.35, respectively, with basal area increments. Furthermore, this study revealed subsequent growth losses in the same year due to defoliation. Our results show that TLS can offer new opportunities to develop new indicators that monitor foliation at the individual tree level. The crown perforation can describe defoliation or the tree’s vitality based on one scanning campaign, whereas the leaf area needed at least two.

Distinguishing pure histopathological growth patterns of colorectal liver metastases on CT using deep learning and radiomics: a pilot study - Martijn P. A. Starmans; Florian E. Buisman; Michel Renckens; François E. J. A. Willemssen; Sebastian R. van der Voort; Bas Groot Koerkamp; Dirk J. Grünhagen; Wiro J. Niessen; Peter B. Vermeulen; Cornelis Verhoef; Jacob J. Visser; Stefan Klein (Clinical & Experimental Metastasis, 2021)
Histopathological growth patterns (HGPs) are independent prognosticators for colorectal liver metastases (CRLM). Currently, HGPs are determined postoperatively. In this study, we evaluated radiomics for preoperative prediction of HGPs on computed tomography (CT), and its robustness to segmentation and acquisition variations. Patients with pure HGPs [i.e. 100% desmoplastic (dHGP) or 100% replacement (rHGP)] and a CT-scan who were surgically treated at the Erasmus MC between 2003–2015 were included retrospectively. Each lesion was segmented by three clinicians and a convolutional neural network (CNN). A prediction model was created using 564 radiomics features and a combination of machine learning approaches by training on the clinician’s and testing on the unseen CNN segmentations. The intra-class correlation coefficient (ICC) was used to select features robust to segmentation variations; ComBat was used to harmonize for acquisition variations. Evaluation was performed through a 100 × random-split cross-validation. The study included 93 CRLM in 76 patients (48% dHGP; 52% rHGP). Despite substantial differences between the segmentations of the three clinicians and the CNN, the radiomics model had a mean area under the curve of 0.69. ICC-based feature selection or ComBat yielded no improvement. Concluding, the combination of a CNN for segmentation and radiomics for classification has potential for automatically distinguishing dHGPs from rHGP, and is robust to segmentation and acquisition variations. Pending further optimization, including extension to mixed HGPs, our model may serve as a preoperative addition to postoperative HGP assessment, enabling further exploitation of HGPs as a biomarker.

Climate hazard indices projections based on CORDEX-CORE, CMIP5 and CMIP6 ensemble - Erika Coppola; Francesca Raffaele; Filippo Giorgi; Graziano Giuliani; Gao Xuejie; James M. Ciarlo; Taleena Rae Sines; José Abraham Torres-Alavez; Sushant Das; Fabio di Sante; Emanuela Pichelli; Russell Glazer; et al. (Climate Dynamics, 2021)

The decline of mussel aquaculture in the European Union: causes, economic impacts and opportunities - Lamprakis Avdelas; Edo Avdic‐Mravlje; Ana Cristina Borges Marques; Suzana Cano; Jacob J. Capelle; Natacha Carvalho; Maria Cozzolino; John Dennis; Tim Ellis; José M. Fernández Polanco; Jordi Guillen; Tobias Lasner; et al. (Reviews in Aquaculture, 2021)
In contrast to the increasing aquaculture production of mussels worldwide, production in the European Union (EU) has shown a decreasing trend over the last two decades. Aquaculture production of mussels in the EU peaked in the late 1990s at more than 600 000 tonnes; by 2016, production volume had dropped by 20% to 480 000 tonnes. As mussel production represents more than ⅓ of EU aquaculture production, this decrease is an important contributor to the stagnation of EU aquaculture. Previous studies have suggested diseases, lack of mussel seed (spat), and low profitability as the main causes of the EU mussel production decrease. In this study, we investigate how economic and environmental factors have contributed. Moreover, we examine if the different mussel production techniques (raft, longline, on‐bottom, and ‘bouchot’) have been differently affected, by analysing the economic performance and cost structure evolution for the period 2010–2016. We complement these results with a SWOT (strengths, weaknesses, opportunities, and threats) analysis of the EU mussel sector based on expert knowledge.

The Effect of Muscle Activation on Head Kinematics During Non-injurious Head Impacts in Human Subjects - Kristen A. Reynier; Ahmed Alshareef; Erin J. Sanchez; Daniel F. Shedd; Samuel R. Walton; Nicholas K. Erdman; Benjamin T. Newman; J. Sebastian Giudice; Michael J. Higgins; James R. Funk; Donna K. Broshek; Thomas J. Druzgal; et al. (Annals of Biomedical Engineering, 2020)

Ecosystem transpiration and evaporation: Insights from three water flux partitioning methods across FLUXNET sites - Jacob A. Nelson; Oscar Pérez‐Priego; Sha Zhou; Rafael Poyatos; Yao Zhang; Peter D. Blanken; Teresa E. Gimeno; Georg Wohlfahrt; Ankur R. Desai; Beniamino Gioli; Jean‐Marc Limousin; Damien Bonal; et al. (Global Change Biology, 2020)
We apply and compare three widely applicable methods for estimating ecosystem transpiration ( T ) from eddy covariance (EC) data across 251 FLUXNET sites globally. All three methods are based on the coupled water and carbon relationship, but they differ in assumptions and parameterizations. Intercomparison of the three daily T estimates shows high correlation among methods ( R between .89 and .94), but a spread in magnitudes of T /ET (evapotranspiration) from 45% to 77%. When compared at six sites with concurrent EC and sap flow measurements, all three EC‐based T estimates show higher correlation to sap flow‐based T than EC‐based ET. The partitioning methods show expected tendencies of T /ET increasing with dryness (vapor pressure deficit and days since rain) and with leaf area index (LAI). Analysis of 140 sites with high‐quality estimates for at least two continuous years shows that T /ET variability was 1.6 times higher across sites than across years. Spatial variability of T /ET was primarily driven by vegetation and soil characteristics (e.g., crop or grass designation, minimum annual LAI, soil coarse fragment volume) rather than climatic variables such as mean/standard deviation of temperature or precipitation. Overall, T and T /ET patterns are plausible and qualitatively consistent among the different water flux partitioning methods implying a significant advance made for estimating and understanding T globally, while the magnitudes remain uncertain. Our results represent the first extensive EC data‐based estimates of ecosystem T permitting a data‐driven perspective on the role of plants’ water use for global water and carbon cycling in a changing climate.

Regional climate downscaling over Europe: perspectives from the EURO-CORDEX community - Daniela Jacob; Claas Teichmann; Stefan Sobolowski; Eleni Katragkou; Ivonne Anders; Michal Belda; Rasmus Benestad; Fredrik Boberg; Erasmo Buonomo; Rita M. Cardoso; Ana Casanueva; Ole B. Christensen; et al. (Regional Environmental Change, 2020)
The European CORDEX (EURO-CORDEX) initiative is a large voluntary effort that seeks to advance regional climate and Earth system science in Europe. As part of the World Climate Research Programme (WCRP) - Coordinated Regional Downscaling Experiment (CORDEX), it shares the broader goals of providing a model evaluation and climate projection framework and improving communication with both the General Circulation Model (GCM) and climate data user communities. EURO-CORDEX oversees the design and coordination of ongoing ensembles of regional climate projections of unprecedented size and resolution (0.11° EUR-11 and 0.44° EUR-44 domains). Additionally, the inclusion of empirical-statistical downscaling allows investigation of much larger multi-model ensembles. These complementary approaches provide a foundation for scientific studies within the climate research community and others. The value of the EURO-CORDEX ensemble is shown via numerous peer-reviewed studies and its use in the development of climate services. Evaluations of the EUR-44 and EUR-11 ensembles also show the benefits of higher resolution. However, significant challenges remain. To further advance scientific understanding, two flagship pilot studies (FPS) were initiated. The first investigates local-regional phenomena at convection-permitting scales over central Europe and the Mediterranean in collaboration with the Med-CORDEX community. The second investigates the impacts of land cover changes on European climate across spatial and temporal scales. Over the coming years, the EURO-CORDEX community looks forward to closer collaboration with other communities, new advances, supporting international initiatives such as the IPCC reports, and continuing to provide the basis for research on regional climate impacts and adaptation in Europe.

Functional colour genes and signals of selection in colour‐polymorphic salamanders - James D. Burgon; David R. Vieites; Arne Jacobs; Stefan K. Weidt; Helen M. Gunter; Sebastian Steinfartz; Karl Burgess; Barbara K. Mable; Kathryn R. Elmer (Molecular Ecology, 2020)
Coloration has been associated with multiple biologically relevant traits that drive adaptation and diversification in many taxa. However, despite the great diversity of colour patterns present in amphibians the underlying molecular basis is largely unknown. Here, we use insight from a highly colour‐variable lineage of the European fire salamander ( Salamandra salamandra bernardezi ) to identify functional associations with striking variation in colour morph and pattern. The three focal colour morphs—ancestral black‐yellow striped, fully yellow and fully brown—differed in pattern, visible coloration and cellular composition. From population genomic analyses of up to 4,702 loci, we found no correlations of neutral population genetic structure with colour morph. However, we identified 21 loci with genotype–phenotype associations, several of which relate to known colour genes. Furthermore, we inferred response to selection at up to 142 loci between the colour morphs, again including several that relate to coloration genes. By transcriptomic analysis across all different combinations, we found 196 differentially expressed genes between yellow, brown and black skin, 63 of which are candidate genes involved in animal coloration. The concordance across different statistical approaches and ‘omic data sets provide several lines of evidence for loci linked to functional differences between colour morphs, including TYR , CAMK1 and PMEL . We found little association between colour morph and the metabolomic profile of its toxic compounds from the skin secretions. Our research suggests that current ecological and evolutionary hypotheses for the origins and maintenance of these striking colour morphs may need to be revisited.

Sekretion von Galektin-3 — Blaupause für die Freisetzung behüllter Viren? - Sebastian Bänfer; Ralf Jacob (BIOspektrum, 2019)

Comprehensive analysis of the in vitro and ex ovo hemocompatibility of surface engineered iron oxide nanoparticles for biomedical applications - Florian Schlenk; Sebastian Werner; Martin Rabel; Franziska Jacobs; Christian Bergemann; Joachim H. Clement; Dagmar Fischer (Archives of Toxicology, 2017)

The Andes Cordillera. Part IV: spatio‐temporal freshwater run‐off distribution to adjacent seas (1979–2014) - Sebastian H. Mernild; Glen E. Liston; Christopher Hiemstra; Andrew P. Beckerman; Jacob C. Yde; James McPhee (International Journal of Climatology, 2017)
The spatio‐temporal freshwater river run‐off pattern from individual basins, including their run‐off magnitude and change (1979/1980–2013/2014), was simulated for the Andes Cordillera west of the Continental Divide in an effort to understand run‐off variations and freshwater fluxes to adjacent fjords, Pacific Ocean, and Drake Passage. The modelling tool SnowModel/HydroFlow was applied to simulate river run‐off at 3‐h intervals to resolve the diurnal cycle and at 4‐km horizontal grid increments using atmospheric forcing from NASA Modern‐Era Retrospective Analysis for Research and Applications (MERRA) data sets. Simulated river run‐off hydrographs were verified against independent observed hydrographs. For the domain, 86% of the simulated run‐off originated from rain, 12% from snowmelt, and 2% from ice melt, whereas for Chile, the water‐source distribution was 69, 24, and 7%, respectively. Along the Andes Cordillera, the 35‐year mean basin outlet‐specific run‐off (L s −1 km −2 ) showed a characteristic regional hourglass shape pattern with highest run‐off in both Colombia and Ecuador and in Patagonia, and lowest run‐off in the Atacama Desert area. An Empirical Orthogonal Function analysis identified correlations between the spatio‐temporal pattern of run‐off and flux to the El Niño Southern Oscillation Index and to the Pacific Decadal Oscillation.

The Andes Cordillera. Part I: snow distribution, properties, and trends (1979–2014) - Sebastian H. Mernild; Glen E. Liston; Christopher A. Hiemstra; Jeppe K. Malmros; Jacob C. Yde; James McPhee (International Journal of Climatology, 2017)
Snow cover presence, duration, properties, and water amount play a major role in Earth's climate system through its impact on the surface energy budget. Snow cover conditions and trends (1979–2014) were simulated for South America – for the entire Andes Cordillera. Recent data sets and SnowModel developments allow relatively high‐resolutions of 3‐h time step and 4‐km horizontal grid increment for this domain. US Geological Survey's Global Multi‐resolution Terrain Elevation Data 2010 topography, Global Land Cover ( GlobCover ), Randolph Glacier Inventory (v. 4.0) glacier, and NASA modern‐era retrospective analysis for research and applications data sets were used to simulate first‐order atmospheric forcing (e.g. near‐surface air temperature and precipitation, including the fraction of precipitation falling as snow) and terrestrial snow characteristics (e.g. snow cover days, snow water equivalent depth, and snow density). Simulated snow conditions were verified against moderate‐resolution imaging spectroradiometer‐derived snow cover extent and 3064 individual direct observations of snow depths. Regional variability in mean annual air temperature occurred: positive trends in general were seen in the high Andes Cordillera, and negative trends at relatively lower elevations both east and west of the Cordillera. Snow precipitation showed more heterogeneous patterns than air temperature due to the influence from atmospheric conditions, topography, and orography. Overall, for the Cordillera, much of the area north of 23°S had a decrease in the number of snow cover days, while the southern half experienced the opposite. The snow cover extent changed ∼−15% during the simulation period, mostly between the elevations of ∼3000 and 5000 m above sea level (a.s.l.). However, below 1000 m a.s.l. (in Patagonia) the snow cover extent increased. The snow properties varied over short distances both along and across the Andes Cordillera.

The Andes Cordillera. Part II : Rio Olivares Basin snow conditions (1979–2014), central Chile - Sebastian H. Mernild; Glen E. Liston; Christopher A. Hiemstra; Jacob C. Yde; James McPhee; Jeppe K. Malmros (International Journal of Climatology, 2017)
Snow cover extent, duration, and properties were simulated (1979/1980–2013/2014) for the Rio Olivares Basin (548 km 2 ) in central Chilean Andes, in an effort to understand conditions and trends (linear) at a basin scale. The National Aeronautics and Space Administration Modern‐Era Retrospective Analysis for Research and Applications products, together with the snow modelling software package SnowModel allowed simulations of first‐order atmospheric forcings (mean annual air temperature ( MAAT ) and water‐equivalent precipitation) and terrestrial snow features (snow cover extent, duration, snow water‐equivalent depth, snow density, and runoff generated from snow melt). Simulated snow cover extent and depletion curves were verified against Moderate Resolution Imaging Spectroradiometer‐derived snow cover data. For the Rio Olivares Basin, MAAT was −2.9 ± 0.6 °C with a mean 0° isotherm at 3325 m a.s.l. The greatest temporal and spatial changes in temperature over the 35‐year period occurred in January and at the highest elevations, respectively. Mean annual precipitation was 1.86 ± 0.60 m w.e., indicating an increase in precipitation of ∼0.1 m w.e. 100 m −1 increase in elevation. On average, ∼90% of the basin precipitation fell as snow, varying from 70% at ∼2600 m a.s.l., to 95% at ∼4200 m a.s.l. In 20 out of 35 years the snow cover extent went to 0% (no basin snow cover) by end‐of‐summer (during March), and the snow duration increased on average by ∼10 days 100 m −1 increase in elevation. Approximately 85% of the basin outlet freshwater runoff originated from snowmelt, making snowmelt a dominant contributor to water resources. Snowmelt‐derived basin runoff was dominated by variability in snow precipitation rather than by variability in MAAT .

Greenland precipitation trends in a long‐term instrumental climate context (1890–2012): evaluation of coastal and ice core records - Sebastian H. Mernild; Edward Hanna; Joseph R. McConnell; Michael Sigl; Andrew P. Beckerman; Jacob C. Yde; John Cappelen; Jeppe K. Malmros; Konrad Steffen (International Journal of Climatology, 2015)
Here, we present an analysis of monthly, seasonal, and annual long‐term precipitation time‐series compiled from coastal meteorological stations in Greenland and Greenland Ice Sheet ( GrIS ) ice cores (including three new ice core records from ACT11D , Tunu2013, and Summit2010). The dataset covers the period from 1890 to 2012, a period of climate warming. For approximately the first decade of the new millennium (2001–2012) minimum and maximum mean annual precipitation conditions are found in Northeast Greenland (Tunu2013 c. 120 mm water equivalent (w.e.) year −1 ) and South Greenland (Ikerasassuaq: c. 2300 mm w.e. year −1 ), respectively. The coastal meteorological stations showed on average increasing trends for 1890–2012 (3.5 mm w.e. year −2 ) and 1961–2012 (1.3 mm w.e. year −2 ). Years with high coastal annual precipitation also had a: (1) significant high number of precipitation days ( r 2 = 0.59); and (2) high precipitation intensity measured as 24‐h precipitation ( r 2 = 0.54). For the GrIS the precipitation estimated from ice cores increased on average by 0.1 mm w.e. year −2 (1890–2000), showing an antiphase variability in precipitation trends between the GrIS and the coastal regions. Around 1960 a major shift occurred in the precipitation pattern towards wetter precipitation conditions for coastal Greenland, while drier conditions became more prevalent on the GrIS . Differences in precipitation trends indicate a heterogeneous spatial distribution of precipitation in Greenland. An Empirical Orthogonal Function analysis reveals a spatiotemporal cycle of precipitation that is linked instantaneously to the North Atlantic Oscillation and the Atlantic Multidecadal Oscillation and with an ∼6 years lag time response to the Greenland Blocking Index.

The significance of deadwood for total bryophyte, lichen, and vascular plant diversity in an old-growth spruce forest - Sebastian Dittrich; Mascha Jacob; Claudia Bade; Christoph Leuschner; Markus Hauck (Plant Ecology, 2014)

Postdiagnosis body mass index and risk of mortality in colorectal cancer survivors: a prospective study and meta-analysis - Sabrina Schlesinger; Sabine Siegert; Manja Koch; Jessica Walter; Nils Heits; Sebastian Hinz; Gunnar Jacobs; Jochen Hampe; Clemens Schafmayer; Ute Nöthlings (Cancer Causes & Control, 2014)

Coastal Greenland air temperature extremes and trends 1890–2010: annual and monthly analysis - Sebastian H. Mernild; Edward Hanna; Jacob C. Yde; John Cappelen; Jeppe K. Malmros (International Journal of Climatology, 2014)
We use observed air temperature data series from 14 meteorological stations in coastal Greenland (located all around the Greenland Ice Sheet) for 1960–2010, where long‐term records for five of the stations extend back to 1890, to illustrate the annual and monthly temporal and spatial distribution of temperature extremes, with the main focus on the latest decade 2001–2010 (2000s). We find that the 2000s had the highest number of mean annual air temperature ( MAAT ) warm extremes, and the 1890s the highest number of cold extremes, and that a high (low) positive North Atlantic Oscillation ( NAO ) Index equals a high number of cold (warm) extreme events. For the 2000s the number of warm extremes was significantly higher by around 50% than the number in the 1940s (the early twentieth century warm period): the latter being the decade with the second highest occurrence of MAAT warm extremes. Since 1960, based on MAAT the number of cold extremes has overall decreased on the decadal timescale, besides a peak in 1980s, while warm extremes have increased, leading to a higher occurrence of extremes (cold plus warm extremes): an almost similar pattern occurred for monthly mean temperatures and monthly mean daily maximum and minimum temperature datasets. Furthermore, a division of Greenland into east and west sectors shows that the occurrence of cold (warm) extremes was more pronounced in the East than in the West in the 1960s and 1970s (mid‐1980s to the 2000s).

Lifestyle factors and health-related quality of life in colorectal cancer survivors - Sabrina Schlesinger; Jessica Walter; Jochen Hampe; Witigo von Schönfels; Sebastian Hinz; Thomas Küchler; Gunnar Jacobs; Clemens Schafmayer; Ute Nöthlings (Cancer Causes & Control, 2014)

Diurnal variations in bacterial and viral production in Cochin estuary, India - Ammini Parvathi; Vijayan Jasna; Keshavan C. Haridevi; Sebastian Jina; Murali Greeshma; Jacob Breezy; Maheswari Nair (Environmental Monitoring and Assessment, 2013)

Storage and eruption of near-liquidus rhyolite magma at Cordón Caulle, Chile - Jonathan M. Castro; C. Ian Schipper; Sebastian P. Mueller; A. S. Militzer; Alvaro Amigo; Carolina Silva Parejas; Dorrit Jacob (Bulletin of Volcanology, 2013)

Significance of Over-Mature and Decaying Trees for Carbon Stocks in a Central European Natural Spruce Forest - Mascha Jacob; Claudia Bade; Héctor Calvete; Sebastian Dittrich; Christoph Leuschner; Markus Hauck (Ecosystems, 2013)

Multi-stage Ag–Bi–Co–Ni–U and Cu–Bi vein mineralization at Wittichen, Schwarzwald, SW Germany: geological setting, ore mineralogy, and fluid evolution - Sebastian Staude; Wolfgang Werner; Teresa Mordhorst; Klaus Wemmer; Dorrit E. Jacob; Gregor Markl (Mineralium Deposita, 2012)

Complement C3 is required for the progression of cutaneous lesions and neutrophil attraction in Leishmania major infection - Thomas Jacobs; Jrg Andr; Iris Gaworski; Sebastian Graefe; Katja Mellenthin; Manfred Krmer; Roman Halter; Jrgen Borlak; Joachim Clos (Medical Microbiology and Immunology, 2005)

Isolation and Characterization of Promoter Regions from Streptococcus gordonii CH1 - Aldwin J.M. Vriesema; Jacob Dankert; Sebastian A.J. Zaat (Current Microbiology, 1999)